Relationship among concentrations of milk urea nitrogen and plasma urea nitrogen and feeding time - Ferdinand, E.E.; Meyer, M. J.; Park, A.F.; VanBaale, M. J.; Titgemeyer, Evan C.; Shirley, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eight Holstein cows were used to determine the relationship among milk urea nitrogen (MUN), plasma urea nitrogen (PUN), and feeding time. We first established that MUN concentrations were similar in concentration among quarters by comparing milk samples from each quarter just before milking. In order to determine if collecting a sample of milk from a quarter influenced the MUN in samples taken later, samples were obtained from the right front quarter (RF) at 2, 4, 6, and 8 hr after the AM milking and from the left front quarter (LF), right rear (RR), and left rear (LR) at 4, 6, and 8 h after the AM milking, respectively. The MUN in samples obtained from RF at 4 hr was lower (P<0.01) than corresponding samples taken from LF, but samples from RF at 6 and 8 hr did not differ from corresponding samples obtained from RR and LR. We concluded that by 6 hr, the effect of previous milking on MUN concentration disappeared because of dilution. To determine the influence of feeding time on MUN concentrations, cows were fed half of their normal PM feeding, injected with oxytocin at the subsequent AM milking to reduce residual milk, and offered surplus feed after the AM milking. Milk samples were collected at 2, 4, 6, 8, 10, and 12 hr after feeding from RF, LF, RR, LR, RF, and LF quarters, respectively. Blood samples were obtained from the coccygeal vein at hourly intervals after feeding with the last sample collected 12 hr after feeding. The MUN concentrations at 2, 4, 6, and 8 hr were similar. The MUN at 10 hr was similar to those at 2 and 8 hr, less than that at 4 and 6 hr, and greater than that for the 12 hr sample. Concentrations of PUN peaked at 2 hr postfeeding, then gradually declined through 12 hr postfeeding. The MUN peaked at 6 hr postfeeding and then declined. Time after feeding significantly influenced PUN and MUN concentrations.
Keywords: Dairy; MUN; PUN; Feeding time